ABIOTIC STRESSORS AND THEIR EFFECT ON THE ACCUMULATION OF ASSIMILATES BY PLANTS AND THE YIELD OF VEGETABLE PEA - O. V. Putina; A. G. Besedin (Труды по прикладной ботанике, генетике и селекции)
Background. Abiotic stressors, such as prolonged dry conditions, oversupply or lack of moisture, frost, etc., are spontaneous, and their impact causes significant damage to plants. This is also true for the common and leafless morphotypes of vegetable pea, which are most widely used in large-scale crop production.Objectives. Eleven cultivars with leaves of  the usual type (common morphotype) and 6 semi-leafless ones (leafless morphotype) were studied.Materials and methods. The experiments were performed on the breeding fields of Krymsk Experiment Breeding Station of VIR (Krasnodar Territory, 2015–2016). The plot area was 10 m2. There were 3 replications. Dry matter content was measured by drying the aerial parts of plants (axial organs, foliar apparatus [leaf, stipules], flowers, unripe beans, pod valves, grain) to constant dry matter at 105°C. Dry matter contents were compared using the t-test. Multifactorial analysis of variance (MANOVA, LSD test) was used to assess the yield of vegetable pea cultivars.Results. Vegetable pea plants are subject to the negative effect of abiotic stressors. With excessive moisture in the initial period of growth, there was a decrease in the accumulation of dry matter in plants. A similar effect is exerted by long absence of precipitation during the growth period of vegetable pea plants from the phase of 2–3 leaves to technical ripeness. The effect of weather conditions during cultivation on the yield of vegetable peas was estimated at 13.3%; and the interaction of the genotype٭environment factors, at 33.3%.Conclusion. No significant differences were observed between the groups of common leafy cultivars and semi-leafless ones in the content of dry matter in the aboveground biomass of plants and the yield. During the two years of research, the cultivars that exceeded the reference in yield were identified: ‘Prima’ (i-155213, Russia) and ‘Ambassador’ (k-9946, Germany), both belonging to the common morphotype.